Returns to citizenship? Evidence from Germany's recent immigration reforms - Gathmann, Christina; Keller, Nicolas (Bonn, 2014)
"Immigrants in many countries have lower employment rates and lower earnings than natives. In this paper, we ask whether a more liberal access to citizenship can improve the economic integration of immigrants. Our analysis relies on two major immigration reforms in Germany, a country with a relatively weak record of immigrant assimilation. For identification, we exploit discontinuities in the reforms' eligibility rules. Between 1991 and 1999, adolescents could obtain citizenship after eight years of residency in Germany, while adults faced a 15-year residency requirement. Since 2000, all immigrants face an 8-year residency requirement. OLS estimates show a positive correlation between naturalization and labor market performance. Based on the eligibility rules, we find few returns of citizenship for men, but substantial returns for women. Returns are also larger for more recent immigrants, but essentially zero for traditional guest workers. Overall, liberalization of citizenship provides some benefits in the labor market but is unlikely to result in full economic and social integration of immigrants in the host country."